LEASINGUL – FORMĂ DE SUSȚINERE A MEDIULUI DE AFACERI - Doga-Mîrzac, Mariana; Caprian, Iulia (CEP USM, 2018)
Atragerea surselor de credit cu o dobândă acceptabilă este actuală pentru investiţiile destinate extinderii şi modernizării procesului de producere. În comparaţie cu întreprinderile mari, cele mici şi mijlocii obţin cu greu credite de lungă durată din cauza lipsei unei asigurări suficiente. O altă problemă ar fi dobânzile foarte ridicate la credite, care le face mai puţin accesibile, acesta fiind un dezavantaj destul de însemnat al întreprinderilor mici şi mijlocii faţă de cele mari. În aceste condiţii, cea mai eficientă modalitate de finanţare pentru mediul de afaceri poate fi numit leasingul. În comparaţie cu variantele alternative de finanţare, procedurile de finanţare prin leasing sunt mult mai simple şi solicită, din partea agentului economic, un aport iniţial de lichidităţi mult mai redus. Întreprinderea poate direcţiona astfel resursele financiare proprii în alte scopuri.

Leases are an important source of funding and allows for easy usage rights on some machines, technological equipment, which leads to increased productivity efficient enterprises. Investment activity is the most important "consumer" external resources. Since the company has more opportunities to finance its activities, the question is to choose those that best fit their needs. This selection is done considering the specific conditions that limit the opportunities for acquiring resources. Bridging the long-term resources can be achieved by resorting to banking, capital markets, specialized companies or state. Since these resources are part of the permanent capital, being found in the financial mechanism of the company for a long period of time, it requires a background relevant financing decision. Compared with alternative financing options, leasing financing procedures are much simpler and calls the operator, an initial cash contribution much lower. The organization may thus direct their financial resources for other purposes.
Keywords: leasing; financial leasing